Chinese Engagement in Hydropower Infrastructure in Sub-Saharan Africa - Jyhjong Hwang; Deborah Brautigam; Nancy Wang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
This paper examines over 100 reported African hydropower projects with Chinese engagement, gleaned from media reports and lists compiled by organizations like AidData and International Rivers. The paper primarily finds that the Chinese are funding considerably fewer large hydropower projects than commonly believed. It also challenges widespread beliefs about Chinese practices, such as the use of resource-backed financing, the lack of social and environmental impact study requirements, and the use of Chinese-only labor. The authors found no evidence to support these assumptions in the hydropower sector.
Keywords: 330